Isolation and diagnosis protocols of Phytophthora spp. applied research approach - Soto Plancarte, Alejandro; Rodríguez Alvarado, Gerardo; Fernández Pavía, Yolanda Leticia; Pedraza Santos, Martha Elena; López Pérez, Luis; Díaz Celaya, Marlene; Fernández Pavía, Sylvia Patricia (Revista Mexicana de Ciencias Agrícolas, 2017)
The purpose of this review is to make known to the researcher, fundamental protocols that are used for the isolation, diagnosis and identification of Phytophthora spp., covering general aspects of the genus for a better understanding and analysis of the same. This information will be useful for researchers working with diseases caused by this oomycete, and is mainly addressed to countries in Latin America. Currently, conventional and molecular methods are used for the detection and identification of Phytophthora species. Conventional methods include the use of taxonomic keys, observation of symptoms and detection of signs of the pathogen in diseased plants, and isolation of the causative agent of infected plant tissue, soil surrounding roots and water sources used for irrigation, using general or selective culture media. Molecular methods provide results that are more accurate in Phytophthora identification and can be performed in shorter time periods and it is not essential that the researcher has experience in aspects of the morphology of members of this genus. It is advisable to integrate the morphological and molecular characterization for the identification, description and taxonomy of Phytophthora .